(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The end of human life is the terminal period. We have prepared this article in order to study the conditions of this period. The article covers the following stages of the terminal state: preagonal state, terminal pause, agony and clinical death. At each stage, functional changes in the body, slowing down biological processes and cessation of vital organs are considered. Also, methods of providing medical care to terminally ill patients, the importance of palliative care and ethical issues are considered.